MED12 mutations in uterine fibroids: their relationship to cytogenetic subgroups - Markowski, Dominique Nadine; Bartnitzke, Sabine; Helmke, Burkhard Maria (International journal of cancer, 2012)
Recurrent chromosomal alterations are found in roughly 20% of all uterine fibroids but in the majority cytogenetic changes are lacking. Recently, mutations of the gene mediator subcomplex 12 (MED12) have been detected in a majority of fibroids but no information is available whether or not they co-occur with cytogenetic subtypes as, e.g., rearrangements of the genes encoding high mobility group AT-hook (HMGA) proteins. In a total of 80 cytogenetically characterized fibroids from 50 patients, we were not only able to confirm the frequent occurrence of MED12 mutations but also to stratify two mutually exclusive pathways of leiomyomagenesis with either rearrangements of HMGA2 reflected by clonal chromosome abnormalities affecting 12q14∼15 or by mutations affecting exon 2 of MED12. On average the latter mutations were associated with a significantly smaller tumor size. However, G>A transitions of nucleotides c.130 or c.131 correlate with a significantly larger size of the fibroids compared to other MED12 mutations thus explaining the high prevalence of the former mutations among clinically detectable fibroids. Interestingly, fibroids with MED12 mutations expressed significantly higher levels of the gene encoding wingless-type MMTV integration site family, member 4 (WNT4). Based on these findings and data from the literature, we hypothesize that estrogen and the mutated MED12 cooperate in activating the Wnt pathway which in turn activates β-catenin known to cause leiomyoma-like lesions in a mouse model. The occurrence of a “fibroid-type mutation” in a rare histologic subtype of endometrial polyps suggests that this mechanism is not confined to uterine leiomyomas.
First published: 05 January 2012
Gesehen am 04.10.2018